PortMeteO flat plate sampler measurements during METEOR cruise M208 - Sebastian Wahl; Simon Speith; Stephanie Fiedler (PANGAEA, 2025)
This dataset describes the non-standard meteorological data collected using the newly developed portable meteorological observatory (PortMeteO) during the METEOR Expedition M208 from Mindelo, Cabo Verde (Feb 13th, 2025) to Mindelo, Cabo Verde (March 17th, 2025). Apart from validating the setup, the main purpose was to observe different properties of Saharan dust outbreaks. The windlidar, flat plate sampler and ceilometer were operated 24/7 while the sun photometers were used at regular intervals during the day whenever clear sky conditions prevailed. Radiosondes were operated at regular intervals between February 19th and March 15th, 2025. Radiosonde launches vary between one every 24h and launches every 3h during dust events or when low-level jets were expected to form.